Delayed presentation of traumatic right diaphragmatic hernia in a child - Mathula Hettiarachchi; Shenal Thalgahagoda (Elsevier, 2022)
Background: Traumatic diaphragmatic hernia is a rare entity in children which could be secondary to blunt or penetrating injury to the abdomen. Due to the presence of other distracting injuries and delayed presentation, diaphragmatic injury could be missed in the initial evaluation. Here we present a case study of a child with a delayed presentation of a right traumatic diaphragmatic hernia following an elephant attack. Case presentation: A 2 year and 7 months old girl was admitted following a tragic elephant attack, with evidence of bilateral lung contusion and right femur fracture. In addition she developed hemoglobinuria complicated with acute renal injury which improved with fluid resuscitation and diuresis. She was ventilated due to respiratory distress and the initial imaging showed normal diaphragmatic margin. On further review there was a lucency in the right hemithorax in the chest x-ray, which appeared to be an eventration in the contrast CT chest. However on laparoscopic examination it was found to be a right traumatic diaphragmatic hernia which was repaired primarily. She was extubated 10 days after the procedure and had an uneventful recovery. Conclusions: Delayed presentation of traumatic diaphragmatic hernia is a known occurrence which could be detected timely by active surveillance of such injury in a child with multiple injuries. Laparoscopy is an important adjunct in the diagnosis of traumatic diaphragmatic hernia in doubtful instances where imaging findings are equivocal.